Integrasi Model PBL, STAD, dan Make a Match dalam Model MERDEKA untuk Meningkatkan Keterampilan Berpikir Kritis Peserta Didik pada Muatan IPAS - Rakasiwi, Sandrina Septia; Jannah, Fathul (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2025)
The problem in this study is the low critical thinking skills of students in IPAS content. This is due to the lack of student participation in critical thinking during learning. Efforts to overcome this problem are to apply the MERDEKA model, which is a combination of the Problem Based Learning, Student Team Achievement Division, and Make a match models. The purpose of this study is to analyze the improvement in students' critical thinking skills. This research is a Classroom Action Research (CAR) conducted over three sessions. The subjects of this study are 10 fourth-grade students at SDN Teluk Tiram 5 Banjarmasin during the second semester of the 2024/2025 academic year. Qualitative data were collected through observations of students' critical thinking skills. The data were analyzed using a qualitative descriptive approach and presented in graphical form. The research findings revealed an increase in students' critical thinking skills from 10% to 80% with the criterion of “Very Skilled.” Based on these findings, the MERDEKA model has proven effective in enhancing students' critical thinking skills and has the potential to serve as a reference in the IPAS learning process.